ANALISIS HUKUM EKONOMI SYARIAH TERHADAP WARALABA (FRANCHISE) PADA BISNIS PENJUALAN TEH POCI DI PULAU BAWEAN - Desy Amiliyah; Abdul Halim (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to evaluate the implementation of Islamic economic law principles in the franchising practices of Teh Poci beverage businesses operating in the Bawean Island region. The business model adopts a franchise system based on an ijarah contract, which involves leasing trademark rights, and is supported by an integrated digital ordering platform and a nationwide logistics delivery service. The study employs a qualitative approach through field research, with data collected via direct observation and in-depth interviews with franchisees. The findings reveal that, in general, the business operations comply with the core principles of Islamic economic law, such as justice, transparency, and mutual consent in the initial contractual agreement. However, in practice, certain deviations from the agreed terms were observed—specifically, some franchisees registered only one business unit but subsequently opened multiple additional branches without the franchisor’s approval. This conduct violates sharia principles concerning contract transparency and compliance with the original agreement, as it exceeds the defined scope and limitations. Such violations suggest a lack of comprehensive understanding of the legal consequences within Islamic contractual frameworks, which are designed to ensure fairness and clarity of rights and obligations for both parties. Therefore, enhanced education and stricter supervision are essential to ensure that franchise business practices remain aligned with sharia principles, and to uphold trust and integrity within business partnerships.